Nigeria's produce marketing boards (Lagos : Nigerian Produce Marketing Co. Ltd.)
This booklet has been produced to show something of the work of these Marketing Boards and something of the export crops which they handle.
ne 15/04/2019
Arch
Keywords: Agricultural commodities; Agricultural economics